Strategi Pemasaran Bisnis UMKM di Masa Pandemic Covid-19 - Fajriyati, Nurul; Nafi' Hasbi, M.Zidny (Rifa'Institute, 2022)
Marketing strategy has an important role in achieving the success of a business, especially at this time of the covid-19 pandemic, a company or MSME is required to maintain its business so that its business does not go out of business and continues even though there is a pandemic. The purpose of this study was to find out how the strategies used in paying attention to the MSME business at the Nada Hijab store during the covid-19 pandemic, and to find out what strategies were applied during the covid pandemic period. The method used in this study is qualitative with a descriptive approach, for data collection in this study using interviews, observation, and documentation. The data analysis technique in this study was carried out through three stages of activities, namely data reduction, data presentation and conclusions/verification. The results of the research regarding the strategy applied at the Nada Hijab store using the 7P marketing mix, where the tone hijab store product in the Pandemic period issued innovations according to the needs of today's society such as masks etc. , always doing live promotions on social media, especially Facebook and always prioritizing friendly and polite service, and during a pandemic more emphasis on online use both on social media and the marketplace.